The Kantian Philosophy as a Procedure to Issue a Judgment - Delgado del Aguila, Jesús Miguel (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
This paper takes up the categories that Kant works in terms of the emission of judgments with respect to taste and aesthetics. For this, it is necessary to consider the method that is configured from the systematization of things and the phenomena involved to obtain its constitution. Likewise, all this is aimed at specifying the concept of aesthetics, so that afterwards the types of judgments that derive from cognitive faculties are understood, such as analytical and synthetic judgments, a priori and a posteriori judgments, determining and reflecting judgments, the aesthetic judgments in the Art and the teleological judgments.